'Global competence' of minority immigrant students: hierarchy of experience and ideology of global competence in study abroad. Issue 1 (2nd January 2020) - Doerr, Neriko Musha
ABSTRACT: In this article, I analyze implications of recent calls to increase minority students' participation in study abroad. I argue, although these calls aim for inclusivity, they frame study abroad as the only way of fostering 'global competence' and imply that minority students lack it. I also highlight the oft-erased global competence nurtured in minority immigrant students' experience. My ethnographic researches of three study abroad trips show that bi/multicultural and bi/multilingual minority immigrant students studying abroad already had global competence and utilized it to enrich their experience. I attribute the lack of acknowledgment of their global competence to the elitist legacy of study abroad, emerging regimes of mobility, and current neoliberal conditions that position races hierarchically. I then suggest new approaches to global competence and study abroad.